Elastic properties of yttrium trioxide doped neodymium lead borotellurite glass system - Mohd Rafien, Siti Nasuha; Hashim, Azhan; Wan Razali, Wan Aizuddin; Laoding, Hasnimulyati; Yahya, Norihan (2024)
This paper presents the influence of transition metal such as yttrium trioxide on the elastic properties of a glass system consisting of (49-x)H3BO3-35TeO2-15PbO-1.0Nd2O3-xY2O3 (0.0≤x ≥2.5 mol%). The glass samples were produced by using melt-quenching method and the elastic properties of the glasses were investigated. X-Ray Diffraction was analyzed to confirm the amorphous nature of the glasses. Longitudinal and shear ultrasonic wave velocities of the glass samples were calculated at room temperature. The calculated density and both ultrasonic wave velocities were employed for measuring elastic moduli, poison’s ratio, microhardness, softening temperature, and Debye temperature. The elastic properties of the glass samples were found to be strongly affected by varying concentrations of yttrium trioxide. The role of the yttrium trioxide modifier in the glass system is clearly demonstrated.